2014
DOI: 10.1159/000360601
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Preservation Outcomes with Different Cochlear Implant Electrodes: Nucleus® Hybrid™-L24 and Nucleus Freedom™ CI422

Abstract: Objectives: In recent years, it has been possible to preserve hearing after cochlear implantation in patients with significant amounts of low-frequency residual hearing. Due to the dimensions and characteristics of the cochlear implants (CIs) Nucleus® Hybrid™-L24 and Nucleus Freedom™ CI422, both can be used to preserve residual hearing. The aim was to investigate the degree and progression of hearing preservation over a longitudinal postoperative period in a large consecutive cohort of implanted patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 19 publications
(24 reference statements)
5
63
0
2
Order By: Relevance
“…After implantation, 78.6%, 57.1%, and 75% of patients had preserved aidable hearing at activation, 6-months, and 12-months, respectively. These rates are comparable with previously published reports with the FLEXsoft and Freedom CI422 (23).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…After implantation, 78.6%, 57.1%, and 75% of patients had preserved aidable hearing at activation, 6-months, and 12-months, respectively. These rates are comparable with previously published reports with the FLEXsoft and Freedom CI422 (23).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Roland et al (22) reported the results of the U.S. clinical trial for the Hybrid-L; though they did not report mean or median threshold elevation data, they reported that 66.6% of patients retained aidable hearing postoperatively (lowfrequency thresholds 85 dB HL). Comparable to our Recognizing that the mean threshold elevation is between 15 and 20 dB for long electrodes following CI, if patients begin with thresholds around 80 dB HL, we must assume they will not have aidable hearing preserved postoperatively (17)(18)(19)23,24). Thus, we analyzed a subgroup of patients who had preoperative thresholds at 250 Hz at 65 dB HL or better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome clearly depends on the length of the electrode as well as the size of the individual cochlea. Insertion depths of less than 18 mm show significantly better hearing preservation than higher insertion depths [40]. The use of local or systemic steroids may also have a protective effect.…”
Section: Cochlea Implant Surgery and Hearing Preservationmentioning
confidence: 97%
“…According to Jurawitz et al [2014], the degree of HL at each interval can be divided into the following 3 groups: pure tone average (PTA) shifts < 15 dB, > 15 to 30 dB, and PTA shift > 30 dB. Additionally, in our study, the percentage of subjects with some measurable postoperative hearing was documented.…”
Section: Discussionmentioning
confidence: 91%